Physical development andnutritional status of young athletes – the pupils of the school of physical training (Environment & Health, 2019)
Objective: According to the norms of the body mass index (BMI) of the Ukrainian schoolchildren, we assessed physical development and nutritional status of the pupils of the boarding school of physical training depending on their gender, age, and kind of sport.Methods: On the basis of the measurement of body weight and height of 1247 pupils (812 boys and 435 girls aged 12–17 years, representatives of 14 kinds of sport) we determined the values of their BMI and compared them with the norms using generally accepted methods.Results: The average values of BMI, individual physical development of 68% of boys and 56% of girls - pupils of all gender and age groups correspond to the normal physical development of the Ukrainian schoolchildren. Pupils aged 14-17 years exceed the children of the region by the average values of BMI, at the age of 12-17 years - by the frequency of normal physical development and especially excess body weight and are characterized by lower frequency of body mass deficiency. At the prevalence of normal physical development in the pupils of all gender and age groups, 13-year-old boys and 12-16-year-old girls are characterized by a significant frequency of body mass deficiency, 16-17-year-old boys and 17-year-old girls – excess body weight. The age dynamics of the average values of BMI and its annual growth in the pupils is consistent with the classical features of the pubertal period in the children of middle and senior school age and it is associated with the pupils’ adaptation to the specific training conditions. Revealed features of physical development and nutritional status of the pupils, engaged in various sports, are associated with the level of their energy expenditures which require a detailed study for the subsequent correction of the nutrition of young athletes.
Keywords: children-athletes; physical development; nutritional status